SIFAT FISIKOKIMIA DAN LAJU DIFUSI PATCH TRANSDERMAL DISPERSI PADAT MELOKSIKAM YANG MENGGUNAKAN NATRIUM LAURIL SULFAT SEBAGAI PENINGKAT PENETRASI - Amalia, Anisa; Nining, Nining; Adiningsih, Jannatu Yasmin (Jurnal Farmasi Udayana; Vol. 11, No. 2, Tahun 2022DO - 10.24843/JFU.2022.v11.i02.p01, 2023)
Meloxicam is a non-steroidal anti-inflammatory medicine (NSAID) with gastrointestinal side effects, hence it's used in transdermal patch preparations as a substitute. Meloxicam was dispersed in PEG 6000 (1:8) and formed as a transdermal patch using sodium lauryl sulfate as a penetration enhancer in this study. The purpose of this study is to see how sodium lauryl sulfate, used as a penetration enhancer, affects the physicochemical characteristics and diffusion of meloxicam in solid dispersion transdermal patches. The patch comes in four different formulas, each with a different concentration of sodium lauryl sulfate: 0% (F0), 1% (F1), 3% (F2), and 5% (F3). The physicochemical parameters of each formula were evaluated, including organoleptic tests, pH, thickness, weight uniformity, moisture content, and folding resistance, as well as diffusion tests. Each formula's transdermal patch has physicochemical characteristics that fulfill the literature's standards. The percentage of meloxicam diffused in each formula was 80.6683 percent, 85.8091 percent, 90.7508 percent, and 93.3322 percent, respectively, with each formula's diffusion rate kinetics following Higuchi's kinetics. The physicochemical characteristics and diffusion rate of the meloxicam transdermal patch were altered by sodium lauryl sulfate (p < 0.05). The most promising patch as an alternative to meloxicam dosage form is meloxicam solid dispersion transdermal patch formulation with 5% sodium lauryl sulfate content.